HUBUNGAN KADAR VITAMIN D DALAM DARAH DENGAN KEJADIAN OBESITAS PADA SISWA SMA PEMBANGUNAN PADANG - Sesmi Nanda Oktavia (Universitas Baiturrahim, 2019)
The obesity cases in the world, including Indonesia is increasing. This condition also occurs to senior high school (SMA) Pembangunan students in Padang. There are several factors affecting the obesity occurrence, one them is the level of vitamin D serum. The aims of this study was to identify the relationship between vitamin D levels in the blood and the obesity occurrence.This research used cross sectional study design from March to June 2017. The samples were 82 students from SMA Pembangunan in Padang conducted by using simple random sampling. The level of obesity was determined by measuring body height and weight. The z zscore BMI/age was calculated by using the WHO antro-plus program while the vitamin D level was measured by ELISA method. The statistical analysis used independent sample t-test.The result shows that there is significant difference of the average vitamin D level in the blood of students with obesity compared to normal students (p=0,025). There is also difference in proportion of obesity occurence between the respondents who lack Vitamin D compared to those with adequate level of vitamin D (p=0,020).Based on the research, it is concluded that there is significant relationship between the level of vitamin D in the blood and the occurrence of obesity. Suggestion further research on the effect of vitamin D on obesity needs to be conducted.